Derivatives of phenyl tribromomethyl sulfone as novel compounds with potential pesticidal activity - Borys, Krzysztof M.; Korzyński, Maciej D.; Ochal, Zbigniew (Beilstein Journal of Organic Chemistry, 2012)
A halogenmethylsulfonyl moiety is incorporated in numerous active herbicides and fungicides. The synthesis of tribromomethyl phenyl sulfone derivatives as novel potential pesticides is reported. The title sulfone was obtained by following three different synthetic routes, starting from 4-chlorothiophenol or 4-halogenphenyl methyl sulfone. Products of its subsequent nitration were subjected to the SNAr reactions with ammonia, amines, hydrazines and phenolates to give 2-nitroaniline, 2-nitrophenylhydrazine and diphenyl ether derivatives. Reduction of the nitro group of 4-tribromomethylsulfonyl-2-nitroaniline yielded the corresponding o-phenylenediamine substrate for preparation of structurally varied benzimidazoles.
Keywords: 2-nitroaniline derivatives; phenylhydrazones; pesticides; SNAr reaction; tribromomethyl sulfone derivatives